Common Laboratory Procedure - Amid, Azura; Jamaluddin, Mohd Jamil Aizat; Othman, Muhd. Ezza Faiez (Springer International Publishing, 2015)
This chapter presents all common laboratory procedures or protocols that researchers normally perform during studies of recombinant enzyme production. The principle and theory behind each experiment is presented to help the reader understand each step that is conducted in an experiment so the reader will be able to select and modify the procedures according to the type of enzyme they are working with. Examples of procedures and the results obtained during recombinant bromelain production are used to develop readers’ understanding